Developing Social Trustworthiness of the Halal Fried Chicken MSMEs’ Value Chain in Malang - Priyo Sugeng Winarto; Puji Akhiroh; Budi Hartono; Nanang Febrianto; Hari Dwi Utami; Khotibul Umam; Juwaidah Sharifuddin (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
The value chain is an essential framework for understanding how industries create and sustain value for consumers or target markets. It encompasses various activities that contribute to delivering valuable products, such as supplier, channel, and buyer value chains. The primary activities in the value chain include inbound logistics, operations, outbound logistics, marketing and sales, and service. This study analyzes the value chain, focusing on halal fried chicken MSMEs, in the Malang Raya. A quantitative descriptive method was employed, involving 56 randomly selected respondents, starting from MSMEs' owners, managers, and operational staff. Data collection techniques included a survey method with questionnaires, in-depth interviews, and observations. The analysis utilized a Likert scale to measure key value chain elements such as inbound logistics, operations, outbound logistics, marketing, and service. The results indicate that the halal value chain ecosystem in Malang Raya is well-established. Respondents agreed that critical activities such as material storage, smooth distribution, product quality control, customer service, and satisfaction significantly impact the success of MSMEs in the region. This study highlights the importance of halal certification and optimal value chain management to enhance product competitiveness in local and international markets. These findings provide insights for policymakers to support the development of the social trustworthiness of the halal value chain ecosystem, ensuring that MSMEs remain competitive in the growing halal food sector.